PENDAMPINGAN DAN PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN INTERAKTIF DENGAN MEMANFAATKAN TEKNIK BERMAIN DALAM PROSES PEMBELAJARAN TATAP MUKA TERBATAS GURU PAUD DAN TK - Jaka Wijaya Kusuma; Hamidah Hamidah; Ahmad Munawir; Ubay Haki; Surtini Surtini; Sanifah Sanifah; Eva Cahya Ningsih (Yayasan Education and Social Center, 2022)
This community service aims to carry out the tri dharma of higher education, realize the work program of the Mathematics Education Study Program, FKIP, Bina Bangsa University and provide socialization about the introduction of interactive media learning that can be an innovation and implemented for PAUD Teachers in the learning process, especially in education during the Covid-19 pandemic. The interactive learning media provided in this training consists of materials that can be applied in early childhood ranging from applications and online platforms to an interactive web that can be accessed easily. This community service activity uses several methods, namely lecture methods, demonstration methods, and question and answer methods, and increases the child's stimulus by playing. Through this training and workshop activity conducted, participants get references to the types of learning media that can be used in improving and maximizing learning, especially in child development and developing character education from an early age